No association between chronotype and cardiovascular response to a cognitive challenge in the morning using a Bayesian approach - Larissa N. Wüst; Christian Cajochen; Ruta Lasauskaite (Neurobiology of Sleep and Circadian Rhythms)
A chronotype is defined as a preference for certain behaviours (e.g., sleep and wake) to occur at specific times of day. It is therefore also temporally linked with cognitive performance across the day. In an exploratory analysis, we sought to find associations between chronotypes determined from self-reported habitual sleep timing and from salivary melatonin onset with mental effort during a 2-back working memory task. Mental effort was operationalized as sympathetic beta-adrenergic impact on the heart, which is best reflected by the cardiac pre-ejection period (PEP) and also influences systolic blood pressure (SBP). Each participant underwent two experimental sessions in the morning: once after sleeping for 8 h and once after sleeping for 5 h the night before. To determine the timing of evening melatonin onset, participants took saliva samples at hourly intervals at home in the evening, prior to their experimental sessions. Chronotypes were determined using reported sleep times from the Munich Chronotype Questionnaire and average melatonin onset during both sleep conditions. Based on this, participants were grouped into early, intermediate, or late types. Neither alertness (BF10 = 0.019), perceived task demand (BF10 = 0.008), nor SBP response (BF10 = 0.268) were credibly impacted by sleep-time derived chronotype, while the association with PEP response (BF10 = 0.631) during a cognitive challenge in the morning was inconclusive. Similarly, the timing of evening melatonin onset did not affect alertness (BF10 = 0.003), perceived task demand (BF10 = 0.006), or PEP or SBP response (PEP: BF10 = 0.232, SBP: BF10 = 0.263) during the cognitive challenge. Our data shows no impact of chronotypes on effort-related cardiovascular response during a cognitive challenge in the morning, which was scheduled according to habitual sleep times.